2004
DOI: 10.1007/s00497-004-0213-0
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of sexual failure in the reproductive processes of a rare bulbiliferous plant, Titanotrichum oldhamii (Gesneriaceae), in subtropical Asia

Abstract: Titanotrichum oldhamii produces both flowers and asexual bulbils on its inflorescences. However, field observations and herbarium collections indicate that seed set is infrequent and that most reproduction is from vegetative bulbils. We have investigated the failure of sexual reproduction and identified four major causes: (1) in the wild, the seed:ovule ratio for open pollination was only 1.9%, in contrast to 10.1% for artificial cross-pollination, implying poor pollinator services. (2) The overall reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Clonality assures offspring establishment, a trait especially important to colonize the bare areas common in arid environments and other extreme habitats where the conditions for sexual reproduction are not always appropriate and organisms depend on stored resources for survival (Lee and Harmer, 1980;Nobel, 1988;Elmqvist and Cox, 1996;Mandujano et al, 2001;Pierce et al, 2003). Given the low probability of sexual establishment (through seeds) for O. microdasys and for other clonal species (Wang et al, 2004), pseudovivipary is a benefit that enhances the permanence of species in extreme habitats (Youngner, 1960;Lee and Harmer, 1980;Arizaga and Ezcurra, 1995;Elmqvist and Cox, 1996;Pierce et al, 2003;Wang and Cronk, 2003). In particular, pseudovivipary in O. microdasys is favored by three factors in all three studied habitats: (1) high fruit abortion that increases the number of fruits on the ground that may develop a root system and become established, (2) parental traits that increase the probability of surviving fruits, and (3) the parent plants generate adequate microenvironmental conditions for the establishment of plantlets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clonality assures offspring establishment, a trait especially important to colonize the bare areas common in arid environments and other extreme habitats where the conditions for sexual reproduction are not always appropriate and organisms depend on stored resources for survival (Lee and Harmer, 1980;Nobel, 1988;Elmqvist and Cox, 1996;Mandujano et al, 2001;Pierce et al, 2003). Given the low probability of sexual establishment (through seeds) for O. microdasys and for other clonal species (Wang et al, 2004), pseudovivipary is a benefit that enhances the permanence of species in extreme habitats (Youngner, 1960;Lee and Harmer, 1980;Arizaga and Ezcurra, 1995;Elmqvist and Cox, 1996;Pierce et al, 2003;Wang and Cronk, 2003). In particular, pseudovivipary in O. microdasys is favored by three factors in all three studied habitats: (1) high fruit abortion that increases the number of fruits on the ground that may develop a root system and become established, (2) parental traits that increase the probability of surviving fruits, and (3) the parent plants generate adequate microenvironmental conditions for the establishment of plantlets.…”
Section: Discussionmentioning
confidence: 99%
“…(2) The development of new plants from vegetative structures such as stems, bulbs, rhizomes, and stolons, that have higher establishment probabilities and can eventually give rise to independent but genetically identical individuals (Callaghan et al, 1992;Arizaga and Ezcurra, 1995;Mandujano et al, 1998;Bobich, 2005). (3) In a number of families (Crassulaceae, Oxalidaceae, Polygonaceae, Saxifragaceae, Agavaceae, Bromeliaceae, Cactaceae, Poaceae, Juncaceae, Liliaceae, and Gesneriaceae), reproductive structures (e.g., a pericarpel or the apex of an inflorescence) can give origin to new clonal individual plants (i.e., pseudovivipary) by means of clonal propagules such as bulbils or plantlets in place of sexual reproductive structures (Youngner, 1960;Elmqvist and Cox, 1996;Diggle et al, 2002;Wang and Cronk, 2003;Cota-Sánchez, 2004;Wang et al, 2004). This last type of vegetative propagation that incorporates sexual structures that fail to produce sexual seeds to produce plantlets has been described as insurance against sexual reproductive failure (Arizaga and Ezcurra, 1995).…”
mentioning
confidence: 99%
“…This nearly complete sexual sterility of G. spathacea Weeda, 2006;Westergård, 1936) is probably no recent acquisition but inherent in the species' state. Wang et al (2004) identified different ecological factors accounting for sexual failure in the rare Gesneriaceae Titanotrichum oldhamii: (1) poor pollinator service, (2) suboptimal environmental conditions, (3) increased inbreeding resulting in low seed set and establishment rates, and (4) resource allocation towards vegetative reproduction (bulbils and rhizome development) rather than fruits. Since G. spathacea is the latest flowering of the German Gagea taxa, the first two factors are probably of minor importance.…”
Section: Is G Spathacea Sexually Sterile?mentioning
confidence: 99%
“…Bulbils have been recorded in many families and also in different clades of single tribes (Givnish & al., 2000;Wang & al., 2004;Thomas & al., 2005;Kitahara & al., 2010) and may have originated in response to strong selection in shady, moist and pollinator-poor habitats (Wake & al., 2011), and indeed the three bulbiliferous species of Urticeae grow mainly in shady habitats along creeks, particularly on wet, dripping cliffs in valleys. This trait probably replaces propagation and dispersal by seeds or fruits.…”
Section: Discussionmentioning
confidence: 99%
“…Bulbils are specialized propagules, allowing vegetative reproduction and dispersal, and many herbaceous plants can produce them (Wang & al., 2004;Walck & al., 2010). Presence or absence of bulbils has been recognized as a significant (Chen & al., 2003).…”
Section: Introductionmentioning
confidence: 99%